Increasing Students’ Motivation by Using Social Networks In And Out of the Classroom - Trajkovic, Vladimir; Vasileva, Marina; Samardzic Jankova, Olga; Karbeva, Slavica; Videnovic, Maja (My University, 2012)
Putting his Majesty computer into schools made tectonic shift of the central pillar in every classroom - the teacher. The threat became bigger with the use of social networks like Facebook and Twitter by the students, as a result of that these sites became forbidden in the schools. But when the students are already there, available in any time and place, why can't we try to direct these users for the benefits of innovative learning and to improve their motivation? The following text will try to investigate the possible answers of this question concerning the benefits from using Facebook and twitter in education as a media for communication between students and teacher. After reviewing the subject of research from the aspect of planned distance education or distance learning which will continue and after the end of the school year, desired data will be obtained. Using the WebQuest method will provide approach to learning from the source of the information distant from the students. Qualitative and quantitative indicators will be presented by the measurement of the achievements and by the students and teacher attitudes.
Keywords: social networks, Facebook, twitter, WebQuest method